IMPROVING THE QUALITY OF LIFE OF DIABETES MELLITUS PATIENTS THROUGH THE USE OF HEALTH APPLICATIONS - Ingenida Hadning; Indriastuti Cahyaningsih; M Rifqi Rokhman; Nabila Uswah Riswana (As-Sidanah, 2024)
The use of health applications is proven to improve the knowledge and quality of life of diabetes mellitus patients. The information on the application is useful in preventing complications due to diabetes mellitus and improving therapy adherence. This community service aims to socialize the use of health applications and discover their effect on increasing knowledge about diabetes mellitus. The method used by this community service is Participatory Action Research (PAR). The partner in this activity is the Pharmaceutical Installation of PKU Muhammadiyah Hospital Bantul. The target of the activity is the elderly group assisted by PKU Muhammadiyah Bantul Hospital. Community service activities have been carried out on Saturday, May 29, 2023, at PKU Muhammadiyah Hospital Bantul. Activities were filled with the implementation of gymnastics, recitation, counselling materials about Diabetes Mellitus and socialization of the use of health applications to improve the quality of life of diabetes mellitus patients. Activities were evaluated through pretests and post-tests and testimonials from participants and activity partners. Participants' knowledge of diabetes mellitus and understanding of health applications also increased, as seen from their pre-test and post-test scores. It can be concluded that this community service activity can increase participants' knowledge of diabetes mellitus and understanding of the use of health applications.